2021
DOI: 10.1016/j.ynstr.2021.100374
|View full text |Cite
|
Sign up to set email alerts
|

Placental DNA methylation marks are associated with maternal depressive symptoms during early pregnancy

Abstract: Maternal depressive symptoms during pregnancy are a significant risk factor for adverse developmental and health outcomes of the offspring. The molecular mechanisms mediating the long-term effects of this exposure are not well understood. Previous studies have found association between prenatal exposure to maternal psychological distress and placental DNA methylation of candidate genes, which can influence placental barrier function and development of the fetus. Our objective in this study was to determine epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In a subset of 581 individuals from the RICHS cohort, 21 imprinted DEGs were associated with maternal depression and anxiety, and 5 imprinted DEGs associated with depression alone, with no differential gene expression in the anxiety only group [ 44 ]. Differential methylation at 2833 CpG sites (FDR < 0.05) was associated with maternal depression at 14 weeks in the FinnBrain Birth Cohort Study ( N = 92) [ 45 ]. Genes closest to these CpG sites were enriched in pathways involving generation and development of neurons [ 45 ].…”
Section: Placental Epigenomics and Prenatal Exposuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In a subset of 581 individuals from the RICHS cohort, 21 imprinted DEGs were associated with maternal depression and anxiety, and 5 imprinted DEGs associated with depression alone, with no differential gene expression in the anxiety only group [ 44 ]. Differential methylation at 2833 CpG sites (FDR < 0.05) was associated with maternal depression at 14 weeks in the FinnBrain Birth Cohort Study ( N = 92) [ 45 ]. Genes closest to these CpG sites were enriched in pathways involving generation and development of neurons [ 45 ].…”
Section: Placental Epigenomics and Prenatal Exposuresmentioning
confidence: 99%
“…Differential methylation at 2833 CpG sites (FDR < 0.05) was associated with maternal depression at 14 weeks in the FinnBrain Birth Cohort Study ( N = 92) [ 45 ]. Genes closest to these CpG sites were enriched in pathways involving generation and development of neurons [ 45 ]. Across these two studies of maternal depression, the gene Erlin2 was identified as a differentially expressed imprinted gene by Litzky et al and as being adjacent to four differentially methylated CpG sites by Lund et al [ 44 , 45 ].…”
Section: Placental Epigenomics and Prenatal Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, epigenetic modifications may also alter fetal gene expression in interaction with other mechanisms; for example, via altering placental functioning (Monk, Spicer, et al, 2012b). Reported epigenetic changes of the placenta emerged in mothers suffering from psychological stress (e.g., Capron et al, 2018; Jensen Peña et al, 2012; Lund et al, 2021).…”
Section: Mechanisms: How Does Prenatal Exposure To Maternal Stress Af...mentioning
confidence: 99%
“…Contrastingly, a meta-analysis of two epidemiological cohorts of predominantly European ancestry found no sign cant associations between prenatal stressful life events and DNA methylation in cord blood 33 . Other agnostic EWASes examining associations with prenatal perceived maternal stress and cord blood DNA methylation 34 or maternal depression during pregnancy and placental DNA methylation 35,36 , also report mixed results. Given the con icting nature of these studies, likely due to population characteristics and/or choice of tissue, there is a need to conduct larger-scaled meta-analyses to increase power, include populations from different genetic ancestries, as well as cultural settings with different levels of maternal stressful life events, and utilize a single tissue sample source for comparison .…”
Section: Introductionmentioning
confidence: 99%